Progressive Muscle Relaxation as an Effort in Reducing Anxiety for Patients with Asthma Attacks - Dewi, Enita; Nisa, Nely Qomarun; Nurmahdianingrum, Sayekti Desi; Triyono, T (Jurnal Berita Ilmu Keperawatan, 2022)
Anxiety occurs in a patient with acute asthma, worsens the symptoms and the conditions and can be at risk of death if not well controlled. The Progressive Muscle Relaxation (PMR) technique reduces anxiety levels in asthmatics patients. This study aimed to analyze the effect of giving PMR on the anxiety level of asthma patients in the Emergency Room (ER). Methods: This quantitative study uses a pre-experimental design with a group pretest-posttest. Samples were obtained through the purposive sampling of 26 adult patients who experienced acute asthma attacks and came to the ER. The instrument used was a Beck Inventory Anxiety (BAI) questionnaire, and the study was analyzed with the Wilcoxon Signed Rank Test. Results: A pre-test intervention found that 46.15% of patients experienced severe anxiety, 46.15% with moderate anxiety, and 7.69% with mild anxiety. After being given the intervention, it changed to 57.69% of patients experienced mild anxiety, 42.31% with moderate anxiety, and none experienced severe anxiety. PMR reduced the anxiety level of asthma attack patients with a p-value of 0.001 (p-value <0.05) and a Z-value of -4.134. Conclusion: PMR can be given as an effort to reduce the anxiety level of patients experiencing asthma attacks. Further research with larger samples is recommended.